(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Domestic violence against males is a serious problem in India, and domestic violence against men has become a major public health concern. This study explores the legal systems that are currently in place to deal with domestic abuse against men in India. The judicial system that is in place in India is analyzed, along with the difficulties and advancements achieved in guaranteeing male victims' access to justice. The advantages and disadvantages of the current domestic violence court system are discussed, as well as suggestions for improving the efficiency of the legal system in handling cases involving male victims of domestic abuse.